Sustainable Value Chain as a Tool for the Development of eSG-Models of Petrochemical Industries - M. V. Vechkasova; A. A. Zubarev; S. Yu. Shevchenko (Мир новой экономики)
The article presents the results of a study aimed at substantiating the need to develop the principles of sustainable development in the oil and gas sector of the economy, which, in turn, determines the change of the raw commodity material model of economic development and the transition to the ESG principles of all enterprises within the industry to ensure the targets of the concept of sustainable development. The search for new ways to manage the added value of the oil and gas sector of the economy is determined by the shift of interests towards renewable energy sources, which limits the use of conventional hydrocarbons and, as a result, leads to a reduction in demand for them. Within the framework of a certain problem, the authors consider the value chain of the oil and gas sector of the economy, taking into account the implemented ESG principles, which allows taking into account the interests of all participants: government-business-science-education. The authors define the current state of industrial development at the point of bifurcation, which necessitates the transformation of existing business models by improving the concept of added value through product life cycle assessment. The authors also identified the principle of emergence of ESG-transition of industrial enterprises, contributing to the widespread introduction and implementation of the principles of sustainable development in the oil and gas sector. In addition, the article discusses circular business models involving the practice of increasing the added value of petrochemical industries by transforming the value chain. Taking into account the regularity of added value from the production cycles of Stan Shi’s product, the authors constructed a «Smiling curve» of changes in added value for the oil and gas sector of the economy, which once again proves that high added value in the oil and gas sector of the economy is created in the petrochemical industries. Taking into account these circumstances, the authors proposed a sustainable life cycle of products of petrochemical industries (using the example of polypropylene).